Whispers of dedication; unraveling motivational narratives among midwives in reproductive healthcare: a qualitative exploration - Khan, Ambareen; Nausheen, Sidrah; Muhammad, Shah; Soofi, Sajid (International Journal Of Community Medicine And Public Health, 2024)
Background: Family planning is an important component of reproductive health care. Midwives play a key role in bridging the gap between community and essential reproductive health services. However, our focus extends beyond their service and deeper into what motivates them in this important area of ​​healthcare. We seek to understand the motivations for their commitment, and the challenges they face in meeting the needs of their patients and communities. Methods: A qualitative study was conducted involving ten midwives with structured guide in a focus group discussion. The interviews were recorded, transcribed, coded and thematic analysis was done. Results: Four themes were derived. The theme “Pinnacle Aspirations" essentially presented the motivation for training as an expression of passionate desire for career advancement and self-interest. “Navigating the Terrain” derived the challenges faced by midwives and their expectations which were limited resources, strong beliefs, and misinformation within the community as well as family resistance hindered contraception intake. “Dismal work realities” portrays midwives’ expectations to be acknowledged in terms of higher salary, position and status in health care system. “Women Empowered” explored midwives’ readiness to raise awareness among women about their rights to choose spacing and appropriate methods available. Conclusions: The study revealed the motivations of midwives and explored the various challenges faced by them and their desire to be acknowledged and rewarded for their invaluable service either through formal recognition of position of authority, monetary incentive or financial support, to aid them in their professional endeavors.